PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS II.B SDN. 004 TERATAK BULUH - Pradila Santi (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This article reports the students' mathematics learning outcomes and learning activities in the classroom. The subjects involved 25 students from class 2B. The research was conducted at SDN 004 Teratak Buluh. The results showed that the implementation of the STAD as a cooperative learning model could improve the mathematics learning outcomes for students at grade 2B of SDN 004 Teratak Buluh. It could be seen from the students’ learning outcomes using the STAD as a cooperative learning model were higher than the students who have not applied the STAD as a cooperative learning model. The improvement of students’ Mathematics learning outcomes from the basic score to the first cycle increased from 65 to 75 with a percentage of 25%. The improvement of students’ Mathematics learning outcomes from the first cycle increased from 75 to 90 with a percentage of 35%. It could be seen that the students’ Mathematic learning outcomes before and after the activities have increased.